The constitutional right to communal justice in Peru. An approach from the Huancané (Puno) Aymaras’ experience - Peña Jumpa, Antonio Alfonso (2016)
This article deals with the conceptualization and implementation of the constitutional rights of the people and human rights through conflict resolution systems in culturally different groups typical experience in Peru is the problem of the so-called “Special Indigenous Jurisdiction” or simply “Communal Justice”; In this sense, we will develop this Community Justice in the light of the experience of the Aymaras in Puno.